Synovial fluid copper and related variables in rheumatoid and degenerative arthritis. - Scudder, P R (1978)
Copper, caeruloplasmin, transferrin, albumin, and total protein were measured in the serum and synovial fluid of 40 patients with rheumatoid arthritis and 40 patients with osteoarthrosis. A raised synovial fluid copper and caeruloplasmin have been found to be characteristic of rheumatoid effusions. The relation between copper and caeruloplasmin in synovial fluid differs from that in serum. Synovial fluid caeruloplasmin was increased disproportionately in relation to other plasma proteins present in rheumatoid effusions.